An Evaluation of Iranian Senior High School EFL CD-ROMs and Its Impact on Teacher Self-Efficacy - Ebrahim Khezerlou (Yayasan Visi Intan Permata, 2025)
The influence of technology on education has become increasingly evident in contemporary EFL classrooms. Educational institutions are progressively integrating technological tools into their activities to improve both instructional practices and student learning outcomes. As supplements to the coursebook, the CD-ROM materials offer novel learning experiences for students in Iranian senior high school EFL classrooms. However, research has not fully established their use, efficiency, and effects in the context. So, the study aims to investigate the extent to which Iranian EFL teachers (n=146) utilize the CD-ROM materials in their classrooms, determine their efficiency, and ascertain their effects on teacher self-efficacy. Two self-developed scales were used to measure the teachers’ use and attitudes about the effectiveness of the EFL CD-ROMs. Moreover, the Teachers’ Self-Efficacy Scale (TSES) developed by Tschannen-Moran and Woolfolk Hoy (2001) was employed to assess the teachers’ self-efficacy beliefs. The results revealed that 71.23% of the teachers frequently used CD-ROM materials in their classrooms. Moreover, the CD-ROMs were highly efficient in terms of Technical Quality, Content Quality, and Instruction Quality, respectively. Finally, the effectiveness of CD-ROM materials positively related to the teachers’ self-efficacy perceptions, while accounting for 36.4% of Engagement, 23.9% of Management, and 10.6% of Instruction.